The Interaction of Top Management Group, Stakeholder, and Situational Factors on Certain Corporate Reputation Management Activities* - Carter, Suzanne M. (Journal of Management Studies, 2006)
abstract This study examines when a firm's members are most likely to promote and defend its reputation. Building on past research in impression management theory and the upper‐echelons perspective, I argue that firms facing increased visibility among different stakeholder groups will increase corporate reputation management activities towards those groups and decrease activities towards other groups. I further argue that top management group characteristics will moderate these relationships, suggesting that certain top management groups are more attuned to the situational needs of reputation management. A set of hypotheses are tested using pooled cross‐sectional time‐series data on a set of Fortune 500 companies. Results indicate that firms generally directed reputation management activities towards their more visible stakeholders. However, the type and extent of reputation management behaviour varied. Specifically, for firms whose top management groups were more highly educated or output oriented, highly visible situations with the media were more likely to be associated with a higher use of press releases. Moreover, those same firms devoted more resources to mass media advertising under situations of high consumer visibility compared to firms whose top management groups were less educated or throughput oriented.